A Typha Angustifolia-Like MoS2/Carbon Nanofiber Composite for High Performance Li-S Batteries - Gu, Xingxing; Kang, Han; Shao, Chengbin; Ren, Xiaolei; Liu, Xiaoteng (Frontiers in Chemistry, 2020)
A Typha Angustifolia-like MoS2/carbon nanofiber composite as both the chemically trapping and redox conversion catalyst for lithium polysulfides have been successfully synthesized via a simple hydrothermal method. By appling the Typha Angustifolia-like MoS2/carbon nanofiber as the interlayer for pure sulfur cathode, the cycling performance and coulombic efficiency have been improved significantly.